Synthesis and characterization of nanoceria for electrochemical sensing applications. Issue 27 (30th April 2021) - Hartati, Yeni Wahyuni; Topkaya, Seda Nur; Gaffar, Shabarni; Bahti, Husein H.; Cetin, Arif E.
Abstract : Nanoceria (cerium oxide nanoparticles: CeO2 -NPs) has received significant attention due to its biocompatibility, good conductivity, and the ability to transfer oxygen. Abstract : Nanoceria (cerium oxide nanoparticles: CeO2 -NPs) has received significant attention due to its biocompatibility, good conductivity, and the ability to transfer oxygen. Nanoceria has been widely used to develop electrochemical sensors and biosensors as it could increase response time, sensitivity, and stability of the sensor. In this review, we discussed synthesis methods, and the recent applications employing CeO2 -NPs for electrochemical detection of various analytes reported in the most recent four years.